2005
DOI: 10.1523/jneurosci.3411-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Few CaV1.3 Channels Regulate the Exocytosis of a Synaptic Vesicle at the Hair Cell Ribbon Synapse

Abstract: Hearing relies on faithful sound coding at hair cell ribbon synapses, which use Ca 2ϩ -triggered glutamate release to signal with submillisecond precision. Here, we investigated stimulus-secretion coupling at mammalian inner hair cell (IHC) synapses to explore the mechanisms underlying this high temporal fidelity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

38
431
3
5

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 284 publications
(477 citation statements)
references
References 47 publications
38
431
3
5
Order By: Relevance
“…This effect has been partly attributed to elevated intracellular Ca 2ϩ from activation of the LTCC. In hippocampal and cerebellar Purkinjie neurons and some sensory neurons, LTCCs may also contribute to normal functions of neurotransmitter release (95)(96)(97)(98)(99). A slower deactivation LTCC tail current in the presenilin mutants during recovery from stress-inducing treatments will result in elevated Ca 2ϩ influx and increased release probability of synaptic vesicles, which is consistent with our observation of the increased EJC amplitude (Supplemental Fig.…”
Section: Discussionsupporting
confidence: 90%
“…This effect has been partly attributed to elevated intracellular Ca 2ϩ from activation of the LTCC. In hippocampal and cerebellar Purkinjie neurons and some sensory neurons, LTCCs may also contribute to normal functions of neurotransmitter release (95)(96)(97)(98)(99). A slower deactivation LTCC tail current in the presenilin mutants during recovery from stress-inducing treatments will result in elevated Ca 2ϩ influx and increased release probability of synaptic vesicles, which is consistent with our observation of the increased EJC amplitude (Supplemental Fig.…”
Section: Discussionsupporting
confidence: 90%
“…3C) and 1.4 for the integral of the AF response (data not shown). A similar linear relation has been shown before at the hair cell synapse (11,(14)(15)(16) and explained by a ''nanodomain model,'' where opening of one Ca 2ϩ channel activates release of only very nearby vesicles (15,17). Thus, as open probability rises with depolarization, each Ca 2ϩ channel's ''cluster'' of vesicles sums to produce a linear dependence on Ca 2ϩ current.…”
Section: Resultssupporting
confidence: 76%
“…This relation is presumed to result from the cooperative binding of three to four Ca 2ϩ ions at the Ca 2ϩ sensor. Similarly, using Ca 2ϩ uncaging and IHC capacitance recordings, Beutner et al (28) found a fifth-order Ca 2ϩ dependence of release, and Brandt et al (15) reported a high apparent Ca 2ϩ cooperativity observed during changes of single channel currents and rapid flicker block. Our data also support the evolving picture that for the physiological relevant voltage range, hair cell synapses operate with a linear Ca 2ϩ dependence of release.…”
Section: Numbers Of Vesicles and Release Ratesmentioning
confidence: 94%
“…Such pooling does not take into account natural cell heterogeneity, but assumes that cells are identical. In another approach, data recorded from all cells have been used to investigate the relation between ∆C m and Q (Brandt et al, 2005), but this analysis neglects that data from different depolarizations applied to the same cell are more strongly correlated than data obtained in different cells, and is likely to overstate the statistical significance of regression coefficients (Venables and Ripley, 2002).…”
Section: Mixed-effects Analysis Of Exocytosis In Mouse β-Cellsmentioning
confidence: 99%